2009
DOI: 10.1073/pnas.0907616106
|View full text |Cite
|
Sign up to set email alerts
|

The inverse and direct Hofmeister series for lysozyme

Abstract: Anion effects on the cloud-point temperature for the liquid؊liquid phase transition of lysozyme were investigated by temperature gradient microfluidics under a dark field microscope. It was found that protein aggregation in salt solutions followed 2 distinct Hofmeister series depending on salt concentration. Namely, under low salt conditions the association of anions with the positively charged lysozyme surface dominated the process and the phase transition temperature followed an inverse Hofmeister series. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

49
551
2
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(604 citation statements)
references
References 56 publications
49
551
2
2
Order By: Relevance
“…There is ample evidence supporting the importance of hydration effects beyond the first hydration shell [40,43,[149][150][151][152][153][154][155][156][157]. The structure and dynamics of interfacial water molecules are different from those in the bulk and exhibit specific ion effects [40,43,[158][159][160][161][162][163].…”
Section: Hofmeister Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…There is ample evidence supporting the importance of hydration effects beyond the first hydration shell [40,43,[149][150][151][152][153][154][155][156][157]. The structure and dynamics of interfacial water molecules are different from those in the bulk and exhibit specific ion effects [40,43,[158][159][160][161][162][163].…”
Section: Hofmeister Effectmentioning
confidence: 99%
“…Stabilization and, in the extreme case, crystallization, are associated with a decrease in the solvent accessible surface of a protein, induced by kosmotropes, whereas destabilization, and, in the extreme case, solubilization, are associated with an increase in the solvent accessible surface. Protein structure is destabilized and function is impaired by cationic electrolyte and polyelectrolyte surfactants, mediated by interfacial water stress [20,21,29,[40][41][42][43][44]85,[148][149][150][151][152][153][154][155][156][157][158][174][175][176][177][178][179][180][181][182][183][184]. Solutes have effects upon the structure of water which extend far beyond the first two hydration shells [149][150][151][152][153][154][155][156][157][185][186][187].…”
Section: Surfactant-induced Interfacial Water Stressmentioning
confidence: 99%
“…Salt ions are categorised according to whether they denature or stabilise a protein [47]. At high salt concentrations, protein-protein interactions become favourable over electrostatic repulsion and this is the driving force for precipitation [48,49] and aggregation [50]. It has also been reported that at low pH, protein-protein interactions become more favourable [51].…”
Section: Influence Of the Aqueous Phase Ionic Strengthmentioning
confidence: 99%
“…Even though they are ubiquitous in the physical, chemical and biological literature, their origin is still contested 1-7 and has been recently brought to the forefront of research [8][9][10][11][12][13][14][15][16][17][18][19] . New work in this area may break down barriers between physics and biology 9 .…”
mentioning
confidence: 99%